THE RISK MANAGEMENT IN THE TOURISM, RURAL TOURISM AND AGRITOURISM - Ioana-Alexandra TOADER; Dorina Nicoleta MOCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
When we think of tourism, one of the economic sectors with the greatest prospects for development, it is inevitable that we do not consider the multitude of risks related to this type of activity. This is why, in order to prevent the catastrophic effects that these risks could generate for both large operators and tourists, it is important to give special importance to risk management. Risk management in this field refers to a complex strategy, aimed at preventing and managing the causes and effects that could generate various crises or imbalances. The aim of this paper is to analyse the main elements that can generate crises or disasters, as well as their effects on the tourist destinations and provide information on the risk management processes for a tourism focused on quality and sustainability.